Prevalence and Association of Obesity, Depression, and Psychological Stress Among the Population of Saudi Arabia - Alreshidi, Nahlah Fahad; Alenzi, Hailah; Alrashidi, Rasha; Aljaloud, Luluh (South Eastern European Journal of Public Health, 2024)
Background: Obesity, stress, and depression are widespread global issues that have a significant impact on people's personal and public health. Studies reveal that the incidence of anxiety and sadness is significantly higher in obese people. Purpose: This study aimed to find ‏the prevalence and association of obesity, depression, and psychological stress among the population of Saudi Arabia. Methods: A cross-sectional study involving the society in general Saudi Arabian population that was conducted. A self-administered questionnaire is disseminated to the populace through an online platform. Results: About 72.1 percent of the 1075 respondents were female, while 52.6 percent were between the ages of 21 and 30. The proportion of obese individuals amounted to 20.6%. In contrast to melancholy (39.4%), psychological tension was present at a prevalence of 77.8%. A statistically significant correlation was observed between stress and depression; however, no such correlation was found between depression and overweight or obesity. Conclusion: Our study indicates that, contrary to what the literature suggests, numerous stressors rather than melancholy may be the cause of obesity rather than a risk factor for the condition. Further investigation is required to ascertain the correlation between psychological tension, obesity, and melancholy.